Industrial Ergonomic Application of Preventing Repetitive Strain Injury to Optimize Work Productivity - Gempur Santoso (PT FORMOSA CENDEKIA GLOBAL, 2023)
Working with excessive repetitive motions experiencing pain is called repetitive strain injury (RSI). Pain is the result of over-moving muscles, nerves, ligaments and tendons. With the occurrence of pain it makes work productivity not optimal. To prevent repetitive strain injuries, it is necessary to make ergonomic adjustments at work. This scientific writing method uses descriptive literature studies. The main purpose of this paper is to understand the ergonomic requirements so as to prevent repetitive strain injury. With repetitive strain injury (RSI) can be prevented with an ergonomic approach, then productivity will be optimal